Relationships between Age, Sex, Laboratory Parameter, and Length of Stay in Patients with Dengue Hemorrhagic Fever - Maria Devi Arianti; J. Prijambodo; Hari Wujoso (Masters Program in Public Health, 2019)
Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by dengue virus. Until now, Dengue virus infection remains a health problem in Indonesia. The things which cause problems in DHF case are high mortality rates, diseases spread which are easily spread, especially affect children. Handling of DHF patients needs long of a length of stay which has large costs.Subjects and Method: This was an analytic observational study with a cross-sectional design. This study was conducted at Dr. Moewardi Hospital, Surakarta, based on medical records. 32 samples were selected using purposive sampling. The independent variables were age, sex, platelet count, hematocrit value, and a number of leukocytes. The dependent variable was the length of stay. The data were obtained from medical records using a Chi-square test. Bivariate analysis was used to determine the factors which affected DHF on length of stay using Chi-square, Kolmogorov Smirnov, continuing with multiple linear regression analysis.Results: The age of DHF patients was from 1 year of age to 53 years of age with an average age of 20.07 +13.45 years. The number of female patients was 15 patients. Platelets level (x 1,000) was 25 for minimum and 308 for maximum. Mean